Protocol for in vitro transfection of mRNA-encapsulated lipid nanoparticles - Kounghwa Youn; Soyeon Yoo; Il Kwon Hwang; Hyunchae Gil; Hayoung Park; Haein Lee; Sunmin Oh; Gyochang Keum; Eun-Kyoung Bang (Cell Press, 2025)
Lipid nanoparticle (LNP) platforms are promising for mRNA therapeutics; however, while highly effective in vivo, commercial mRNA-LNPs show reduced transfection efficiency in vitro under serum-starved conditions, limiting mechanistic studies and cell engineering applications. Here, we present a new standard for in vitro transfection of mRNA-LNPs, including cell culture preparation, mRNA-LNP treatment in complete media, and mRNA expression level quantification. This protocol improves efficiency and reproducibility in in vitro screening and ensures consistency in the assessment of mRNA-LNPs.